Penerapan Undang-Undang Tentang Lalu Lintas Dan Angkutan Jalan Dapat Mengurangi Kecelakaan Lalu Lintas - Rizky Setiawan (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
The number of traffic accident fatalities in Indonesia remains a serious issue that requires thorough attention. Law No. 22 of 2009 on Traffic and Road Transportation (UULLAJ) was designed to reduce the number of accidents and improve road safety. This article aims to evaluate the implementation of this law in efforts to lower traffic accident fatalities. Using a qualitative analysis method, this study assesses the effectiveness of traffic regulations, government policies, as well as the supporting and inhibiting factors in its implementation. The research findings show that despite the regulations being enforced, challenges remain in law enforcement and public awareness levels. Therefore, increased cooperation between authorities and the public is necessary to ensure more effective rule enforcement in order to reduce the number of fatalities from accidents.